A pilot study of actigraphy as an objective measure of SSRI activation symptoms: Results from a randomized placebo controlled psychopharmacological treatment study. Issue 3 (28th February 2015) - Bussing, Regina; Reid, Adam M.; McNamara, Joseph P.H.; Meyer, Johanna M.; Guzick, Andrew G.; Mason, Dana M.; Storch, Eric A.; Murphy, Tanya K.
Abstract: Selective serotonin reuptake inhibitors (SSRIs) are an efficacious and effective treatment for pediatric obsessive-compulsive disorder (OCD) but have received scrutiny due to a potential side effect constellation called activation syndrome. While recent research introduced a subjective measure of activation syndrome, objective measures have not been tested. This pilot study, using data from a larger randomized-controlled trial, investigated the potential of actigraphy to provide an objective measure of activation symptoms in 44 youths with OCD beginning an SSRI medication regimen. Data were collected over the first four weeks of a multi-site, parallel, double-blind, randomized, placebo controlled psychopharmacological treatment study and statistical modeling was utilized to test how activation syndrome severity predicts daily and nightly activity levels. Results indicated that youths with higher activation symptoms had lower daytime activity levels when treatment averages were analyzed; in contrast youths who experienced onset of activation symptoms one week were more likely to have higher day-time and night-time activity ratings that week. Results support actigraphy as a potential objective measure of activation symptoms. Subsequent studies are needed to confirm these findings and test clinical applications for use by clinicians to monitor activation syndrome during SSRI treatment. National Institutes of Health (5UO1 MH078594-01); NCT00382291. Highlights: Actigraphy could be an objective measure of activation syndrome in children on SSRIs. We model the prospective association of activation syndrome and day/night activity levels. Week-to-week increases in activation syndrome were mirrored by increases in activity levels. Children who experienced more activation syndrome during treatment had lower activity levels.